Multiple-omics analysis of three novel haloalkaliphilic species of Kocuria revealed that the phenolic acid-degrading abilities are ubiquitous in the genus - Xu, Lian; Sun, Rui-Qi; Zeng, Jia-Hui; Wei, Hua-Mei; Shen, Biao; Sun, Ji-Quan (Frontiers in Microbiology, 2025)
Phenolic acids (PAs), which can exert toxic effects on seed germination and plant growth, are the most common allelopathic substances found in soils. To better understand the degradation fates of PAs in the rhizosphere of halophytes, five haloalkaliphilic PA-degrading bacteria, which were identified as three novel species of Kocuria (namely, Kocuria rhizosphaerae sp. nov., Kocuria kalidii sp. nov., and Kocuria rhizosphaericola sp. nov.), were obtained from the rhizosphere and bulk soil of the halophyte Kalidium cuspidatum. All five Kocuria strains could efficiently degrade ferulic acid (FA) and cinnamic acid (CA) under saline-alkaline conditions. Genomic and transcriptomic analyses revealed that the acrylic groups of FA and CA were first converted to a carboxyl via the coenzyme A (CoA)-dependent non-β-oxidation pathway by the five Kocuria strains. However, the five Kocuria strains selected different aromatic ring-cleavage ways for the degradation of the benzoic derivatives intermediates of the two compounds. The protocatechuate result from FA was then thoroughly degraded through an aromatic ring-opening reaction catalyzed by protocatechuate 3,4-dioxygenase (PcaGH), and the β-ketoadipic acid pathway. At the same time, the yield of benzoate originated from CA was subsequently converted to catechol by the benzoate 1,2-dioxygenase system (BenABCD) or phenylacetyl-CoA epoxidase (PaaABCD) and further completed the ring-cleavage by catechol 1,2-dioxygenase or catechol 2,3-dioxygenase (two non-PcaGH dioxygenases). The comparative genomic analysis revealed that the genes for phenolic acids hydroxylation, protocatechuate 3,4-dioxygenation, and those involved in the β-ketoadipic acid pathways are universal in the Kocuria strains. It is also demonstrated that the Kocuria strains maintain their osmotic balance by accumulating potassium, rather than biosynthesizing organic osmoprotectants, under hypersaline conditions.